Accurately extracting the signature of intermolecular interactions present in the NCI plot of the reduced density gradient versus electron density. Issue 27 (30th June 2017) - Lefebvre, Corentin; Rubez, Gaëtan; Khartabil, Hassan; Boisson, Jean-Charles; Contreras-García, Julia; Hénon, Eric
Abstract : A new model for reference electron densities, really getting rid of interactions. Abstract : An electron density (ED)-based methodology is developed for the automatic identification of intermolecular interactions using pro-molecular density. The expression of the ED gradient in terms of atomic components furnishes the basis for the Independent Gradient Model (IGM). This model leads to a density reference for non interacting atoms/fragments where the atomic densities are added whilst their interaction turns off. Founded on this ED reference function that features an exponential decay also in interference regions, IGM model provides a way to identify and quantify the net ED gradient attenuation due to interactions. Using an intra/inter uncoupling scheme, a descriptor (δ g inter ) is then derived that uniquely defines intermolecular interaction regions. An attractive feature of the IGM methodology is to provide a workflow that automatically generates data composed solely of intermolecular interactions for drawing the corresponding 3D isosurface representations.